Halobacillus ihumii sp. nov., a new bacterium isolated from stool of healthy children living in Mali. (September 2020) - Konate, S.; Lo, C.I.; Kuete, E.; Sarr, M.; Amsrtong, N.; Levasseur, A.; Caputo, A.; Thera, M.A.; Raoult, D.; Million, M.
Abstract: Strain Marseille-Q1234 T is a new species from the genus Halobacillus that was isolated in 2019 from a stool sample in a healthy Malian child <5 years old. Cells are Gram-positive and strictly halophilic bacilli. Strain Marseille-Q1234 T exhibits 98.46% 16S rRNA gene sequence similarity to Halobacillus naozhouensis strain JSM 071068 T (NR_116505.1), the phylogenetically closely related species with standing in nomenclature. Based on the phenotypic and phylogenetic evidence, OrthoANI values and results of the biochemical tests, the new species is named Halobacillus ihumii sp. nov., for which strain Marseille-Q1234 T (= CSURQ1234) is proposed as the type strain.